Deightoniella mayeei sp, novo and Dischloridium gangawanei sp. novo from Andhra Pradesh, India - NK RAO; O.K. AGARWAL, C. MANOHARACHARY, I.K. KUNWAR, (Indian Phytopathology, 2007)
During a survey of inicrofungi from diversified habitats, two novel dematiaceous hyphomycetes were collected from the forests of Andhra Pradesh. In Deightoniella mayeei sp. novo globose-subglobose, percurrent conidiogenous cells produce obovoid, two celled conidia. In Dischloridium gangawanei sp. novo conidia are broadly ellipsoid or bowl shaped, one celled with one setula at each end.